Technology-Based Shared Story Reading for Students With Autism Who Are English-Language Learners. Issue 2 (June 2017) - Alison, Caryn; Root, Jenny R.; Browder, Diane M.; Wood, Leah
Demonstrating comprehension of text is a complex skill that is an area of difficulty for many students with autism spectrum disorder (ASD). Shared story reading is an intervention that has a history of effectiveness in teaching literacy skills to students with extensive support needs. This study used a multiple probe across participants design to evaluate the effects of shared story reading using e-texts and embedded prompting on vocabulary and reading comprehension of grade-aligned narrative texts by elementary students with ASD who were also English-language learners. Outcomes indicate shared story reading with the embedded technological supports was effective for teaching comprehension of WH questions as well as identification of WH rules and definitions. Implications for future research and practice are discussed.